Vocabulary from 1735 Lithuanian translation of the Bibel in the dictionary of Pilypas Ruigys - Zubaitienė, Vilma (Lietuvių kalba, 2018)
This article examines the use of biblical vocabulary in Pilypas Ruigys’ dictionary „Littauiſch=Deutſches und Deutſch=Littauiſches Lexicon“ (Königsberg 1747). The biblical words in this dictionary were derived from the 1735 Lithuanian translation of the Bibel. This fact is clearly stated in the title of the dictionary. Moreover, in the foreword to the dictionary the author highlights that he attempted to pick out as many Lithuanian synonyms from the Holy Script as possible. The exact chapters and verses of the Bible referenced next to the Lithuanian words help to determine which words and multi-word expressions were included in the dictionary. To this day there hasn’t been a statistical and textual analysis, which would show the nature and scale of the Bible references in Ruigys’ dictionary. The analysis has shown that Ruigys refered to the Bible mostly in search of suitable translation of German words and multi-word expressions. In addition, the Bible was a source for expanding the list of lemmata of German-Lithuanian part of the dictionary. The biblical references are in most cases placed next to the single words or two-word (in rare cases three-word) expressions that refer to some kind of Biblical terminology, i.e. name of a person, a thing or an occurence. There are very few longer citations of the Bible. Approximately 3500 words and multi-word expressions were copied from the Old Testament and about 650 – from the New Testament. Book of Genesis was referenced most times (more than 350), more than 200 examples were taken from Book of Exodus, Psalms, Book of Isaiah and Book of Job. The most cited part of the New Testament was the Book of Matthews.